The Influence of Web-Based Hospital Nurse Caring Information System Applications as An Effort to Increase Knowledge and Caring Attitudes of Nurses - Any Yuliani; Iwan Purnawan; Suratman Suratman (GLOBAL HEALTH SCIENCE GROUP, 2024)
Caring is a dynamic approach, where nurses work to increase their care for clients. Nurses' knowledge and caring attitude are the things that underlie nurses in applying caring behaviour. Objective: to determine the effect of SI CAPERS application as an effort to increase nurses' knowledge and caring attitude in the ICU Room of RSI PKU Muhammadiyah Tegal. Method: Research study and the effect of application and quasy experiment with non equivalent control group design. The application was tested by questionnaire for usability and Aiken V test for material and media. Paired Sample T Test was used to analyse data on nurses' knowledge and caring attitude. The population of this study was all ICU/HCU nurses at RSI PKU Muhammadiyah Tegal. The sample taken was 34 people consisting of 17 ICU nurses as the intervention group and 17 nurses as the control group. Results: The results of the SI CAPERS application questionnaire are very feasible at 92.5% and 0.841 according to the objectives, material, methods, sources and learning activities with an easy, attractive and simple design. Data analysis resulted after the intervention there was an effect of the SI CAPERS application as an effort to increase knowledge and caring attitudes of nurses p - value <0.006. Conclusion: SI CAPRES application is able to improve the knowledge and caring attitude of nurses in the ICU Room of RSI PKU Muhammadiyah Tegal.